Marketing proactiveness strategies and service quality synergy: a pathway to marketing excellence in private banks in Iraq - Rashid, Shirin; Mousa, Kawar Mohammed; Ahmed, Dildar Haydar; Ali, Khairi Ali Auso (Frontiers in Communication, 2026)
Marketing excellence refers to a firm’s ability to consistently create superior customer value through strong marketing capabilities and translate this into sustainable outcomes such as customer retention, market performance, and competitive positioning. In Iraq, private banks in Erbil face rising pressure to anticipate change, respond quickly, and deliver reliable service quality in a market where customer trust is central. This study examines how six marketing proactiveness strategies, trend anticipation and innovation, customer-centric approach, competitive intelligence, agile marketing practices, strategic partnerships and collaborations, and content and thought leadership, contribute to marketing excellence, and whether service quality strengthens these relationships. A quantitative design was employed using survey data from 410 bank officers across 32 private banks in Erbil. After obtaining organizational access approvals, proportional selection was applied within banks to ensure representation across top, middle, and lower management levels, with random selection used to identify participating officers. Structural equation modeling was used to test the hypotheses and the moderating role of service quality. Results indicate that marketing proactiveness strategies positively influence marketing excellence, while service quality strengthens several of these relationships, with conditional effects varying across strategy dimensions. The study contributes by extending the resource-based view through a capability-bundling explanation of how proactive marketing and service quality jointly support marketing excellence in an underexplored banking context.